Translocation of an unusual cAMP receptor to the nucleus during development of Dictyostelium discoideum. - Kay, C A (1987)
cAMP has been implicated in the control of the expression of developmental genes in Dictyostelium discoideum. To determine the potential role of cAMP receptors as regulators of gene expression, we have used immunocytochemical and immunoblotting techniques to reveal the subcellular localization of a cAMP binding protein CABP1. Most of the CABP1 antigen in early developing cells is localized near the cell periphery, with a small amount found in the nucleus. The level of CABP1 in the nucleus increases approximately 30-fold during development. Moreover, immunofluorescence studies showed that CABP1 can also be detected on the cell surface. Binding of anti-CABP1 to intact cells followed by reaction with 125I-labeled secondary antibody revealed that the cell-surface CABP1 activity peaks during aggregation and culmination. In addition, several proteins related to CABP1 are found mainly in the nuclear fraction of developing cells. The possible role of these proteins in the regulation of developmental gene activity is discussed.